Plant trait-based life strategies of overlapping species vary in different succession stages of subtropical forests, Eastern China - Liu, Libin; Xia, Haojun; Quan, Xinghua; Wang, Yunquan (Frontiers in Ecology and Evolution, 2023)
Plants growing in forests at different succession stages in diverse habitats may adopt various life strategies from the perspective of plant functional traits. However, species composition differs with forest succession, and the effects of forest succession on traits have often been explored without considering the effects of species identity. We comprehensively investigated intraspecific variations in 12 traits of six overlapping species (two tree species and four understory shrub species) in three typical subtropical evergreen broad-leaved forests at different succession stages in eastern China. We found that intraspecific variations differed among traits. Fine root specific length presented large intraspecific variation, leaf area, specific leaf area and fine root tissue density showed medium intraspecific variations, and other traits displayed small intraspecific variations. Trees and understory shrubs in the early-stage forest exhibited higher leaf thickness, dry matter contents and tissue densities of leaves, roots, twigs, and stems and lower leaf area and specific leaf area. Those in the medium- and late-stage forests displayed contrasting trait characteristics. From the perspective of plant functional traits, plants in the early-stage forest formed a series of trait combinations for a resource conservative strategy with a low growth rate to adapt to fragile habitats with poor soil nutrients and changeable soil temperature and humidity, and those in the medium- and late-stage forests (especially the former) formed converse trait combinations for a resource acquisitive strategy with a high growth rate to adapt to low light availability and strongly competitive habitats. Our study reveals that plants in forests at different succession stages adopt various life strategies and provides data to the TRY and China plant trait databases.